CHILDHOOD CANCER KNOWLEDGE AMONG PARENTS WHOSE CHILDREN ARE ON ADMISSION AT THE PAEDIATRIC WARD OF TAMALE TEACHING HOSPITAL (TTH) - Muktar, A. M.; Salifu, A.; Deme-Der, S.; Ayiwor, G. A. (UDS International Journal of Development, 2023)
There is an upsurge in childhood cancers in recent times, with low survival rates especially in most Low and Middle-Income Countries (LMICs). Most deaths in these developing countries are avoidable since there are cost-effective treatments available. Over the years, a lot of research has been conducted into childhood cancers, but little has been done to assess the knowledge of parents on childhood cancer. Knowledge of parents is prerequisite in seeking early treatment. This study, therefore, sought to assess the knowledge of parents on childhood cancer of their children diagnosed with cancer at the Tamale Teaching Hospital in Ghana. The specific research objectives were centred on the level of knowledge of the parents on cancer among children; parents’ knowledge on the cause of childhood cancer and how parents think cancer can be managed in children. An exploratory qualitative research design was used. A simple random sampling technique was implored to select participants. A semi-structured interview, with the aid of an interview guide w as used to solicit information from 15 participants; which was audio-taped and later transcribed verbatim and analysed using thematic content analysis method. The results showed that the parents had little knowledge on the cause of childhood cancer. As a consequence, they had limited knowledge on general management of cancer among children. However, they appeared to have a fair knowledge on the general cause of childhood cancer. It is recommended that Ghana Health Service should provide more health education on childhood cancers as well as encourage parents to report such cases early to treatment centres across the country. Keywords: Cancer, Parent, Knowledge, Childhood, Treatment.